Gestión administrativa y su incidencia en el sistema de control presupuestario de la dirección distrital 13D08 Pichincha- educación, año 2014, Guía de control presupuestario. - Mendoza Intriago, Johanna Elizabeth (2015)
This research was conducted in the District Direction 13D08 PichinchaEducation, whose main activity strengthen and direct educational services the educational community, serving local and cultural realities of the cantoPichincha. Its objective is focused on assessing the impact of the administration in thbudget control system of the District Direction 13D08 Pichincha - Educatiobased on the question: What is the impact of administrative management the system of budgetary control of the District Direction 13D08 PichinchaEducation? It is important to state that there is little knowledge of the administrativhandling by staff, which makes the operating and administrative budget linand controlling financial activities; and thus the proper implementation integrated public finance system. The hypothesis corresponds to an inadequate administration that adverselyaffects the system of budgetary control 13D08 Pichincha District DirectionEducation, in order to demonstrate the above variables in the problem of stud Education - Based on the described problems developing a guide to budgcontrol will correct the deficiencies, contributing to the achievement corporate goals and quality of public spending Pichincha District Directoratintends 13D08. In addition, this thesis seeks to raise awareness among managers of pubinstitutions on the importance of representing the staff selected with skills aexpertise in administrative management for the proper development activities, being the axis of the point in the organizations success.